Single versus bilateral external ventricular drainage for intraventricular fibrinolysis in severe ventricular haemorrhage. Issue 1 (17th December 2009) - Staykov, D; Huttner, H B; Lunkenheimer, J; Volbers, B; Struffert, T; Doerfler, A; Ganslandt, O; Juettler, E; Schwab, S; Bardutzky, J
Abstract : Background: Intraventricular fibrinolysis (IVF) through bilateral external ventricular drains (EVD) may provide better access of the thrombolytic agent to the intraventricular clot, potentially influencing clot clearance and outcome. Methods: Patients with spontaneous ganglionic intracerebral haemorrhage (ICH)<40 cm 3 and intraventricular haemorrhage (IVH) with acute hydrocephalus have been treated with IVF. The decision for placement of one or two EVDs has been left to the discretion of the treating physician. CT volumetry, the effects on cerebrospinal fluid (CSF) circulation and outcome at 3 months have been analysed for patients with one (group I, n = 13) or two EVDs (group II, n = 14). Results: No difference was found in clot resolution between the two groups (clot half life 2.1 (SD 1.2) vs 2.4 (1.3) days). A separate analysis of the third and fourth ventricle clearance was similar (1.6 (0.6) versus 1.8 (0.8) days), indicating no difference in reconstitution of CSF circulation. A trend towards a longer EVD duration and higher infection rate was found in the bilateral EVD group. No difference was found in outcome at 3 months. Conclusions: Our results do not support the use of bilateral EVDs for IVF in patients with severe IVH.